A Study on Role of Competencies in HRM in IT Industry with Special Reference to Pune District: Exploring the Impact of IT Competencies on HRM Practices in the IT Industry: A Study in Pune District (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose is to understand the function of IT competence as an independent variable in activating Human Resources Management Practices (HRM practices) as a dependent dimension variable (IT usages, IT knowledge and IT operation) (HRM practices) (Training and Development, Recruitment, Job Design, and Performance appraisal). Based on this, two basic hypotheses are formulated to identify correlations and linkages between the independent and dependent variables. The connection of IT competence with HRM practices within the dimensions is substantial and has an influence. In addition, the Informatics and Communication Public Company in Pune is the scope and population of this investigation. To analyze the correlations between variables, a quantitative design technique was used and the researcher used the descriptive-analytical technique. A number of workers and management (responder) were provided with the questionnaire, they have been randomly picked and 76 respondents included. The Statistical Program (SPSS) has been used for the analysis of the data, using statistical and descriptive methods such as mean, variation coefficient, and default variance, to analyze and describe correlation hypothesis data and to test the impact hypothesis by using a simple linear regression coefficient. The main outcomes of this study showed that the association between HRM practices is linked to IT skills, and hence there is an efficient connection of research variables.